Inside out [videorecording (DVD)] - Docter, Pete; Poehler, Amy, 1971-; Hader, Bill, 1978-; Black, Lewis, 1948-; Kaling, Mindy (Disney, 2015)
Growing up can be a bumpy road, and it's no exception for Riley, who is uprooted from her Midwest life when her father starts a new job in San Francisco. Like all of us, Riley is guided by her emotions ; Joy, Fear, Anger, Disgust, and Sadness. The emotions live in Headquarters, the control center inside Riley's mind, where they help advise her through everyday life.